Caracterização e propriedades catalíticas da zeolita HZSM5 modificada com nióbio - Florentino, A. O. [UNESP]; Saeki, M. J. [UNESP]; Cartraud, P.; Magnoux, P.; Guisnet, M. (Sociedade Brasileira de Química, 1997)
HZSM5 zeolite was modified by exchanging proton by niobium (V). Several samples were obtained with various degrees of exchange. Pore volumes and acidity were measured to characterize these exchanged zeolites. Catalytic properties were evaluated with two reaction tests: m-xylene transformation and n-heptane cracking. The introduction of niobium on HZSM5 zeolite decreases the diffusion coefficient of 2-methyl-pentane and increases the zeolite acidity. The sample containing niobium are initially more active in cracking of n-heptane and m-xylene isomerization than HZSM5 alone.
Characterization and catalytical properties of hzsm5 zeolite modified by niobium
Keywords: HZSM5 zeolite; niobium exchange; pore volume; acidity